2001
DOI: 10.1002/1522-2675(20010815)84:8<2243::aid-hlca2243>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Optically Active Cyclophane Receptors for Mono- and Disaccharides: The Role of Bidentate Ionic Hydrogen Bonding in Carbohydrate Recognition

Abstract: A new family of optically active cyclophane receptors for the complexation of mono-and disaccharides in competitive protic solvent mixtures is described. Macrocycles (À)-(R,R,R,R)-1 ± 4 feature preorganized binding cavities formed by four 1,1'-binaphthalene-2,2'-diyl phosphate moieties bridged in the 3,3'-positions by acetylenic or phenylacetylenic spacers. The four phosphodiester groups converge towards the binding cavity and provide efficient bidentate ionic H-bond acceptor sites (Fig. 2). Benzyloxy groups i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
41
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(42 citation statements)
references
References 28 publications
1
41
0
Order By: Relevance
“…The smaller SPM 65 was capable of selective carbohydrate recognition with several glucopyranosides, with modest enantioselectivity observed in some cases. Later generations of SPMs built on this same concept incorporated larger carbon scaffolds and modified receptor sites such as phosphate ester 67 shown below, a molecule that bonded selectively to disaccharides[69][70][71][72].Kawase, Oda, and coworkers have synthesized a unique series of belt-shaped paraphenylacetylene macrocycles 68-71 (Scheme 6.18A) and studied their hostguest supramolecular chemistry. The precursor polyenes 72-75 were synthesized using a modified McMurry reaction, and a subsequent bromination/dehydrobromination sequence with t-BuOK gave the desired SPMs 68-71.…”
supporting
confidence: 82%
“…The smaller SPM 65 was capable of selective carbohydrate recognition with several glucopyranosides, with modest enantioselectivity observed in some cases. Later generations of SPMs built on this same concept incorporated larger carbon scaffolds and modified receptor sites such as phosphate ester 67 shown below, a molecule that bonded selectively to disaccharides[69][70][71][72].Kawase, Oda, and coworkers have synthesized a unique series of belt-shaped paraphenylacetylene macrocycles 68-71 (Scheme 6.18A) and studied their hostguest supramolecular chemistry. The precursor polyenes 72-75 were synthesized using a modified McMurry reaction, and a subsequent bromination/dehydrobromination sequence with t-BuOK gave the desired SPMs 68-71.…”
supporting
confidence: 82%
“…C arbohydrate recognition is an active area of supramolecular chemistry, motivated by the biological importance of saccharides and also by the unusual challenge represented by these complex substrates (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). On the one hand, carbohydrates must be recognized and processed during metabolism, whereas saccharide motifs are known to mediate cell-cell recognition, the infection of cells by pathogens, and many aspects of the immune response (14)(15)(16)(17).…”
mentioning
confidence: 99%
“…On the other, carbohydrates possess structures that are fairly large, irregular, and multivalent, while being quite similar to clusters of water molecules. Even in nonpolar solvents, selective carbohydrate receptors require extended, sophisticated architectures (1,(3)(4)(5)(6). In the presence of liquid water, the problem becomes yet more difficult.…”
mentioning
confidence: 99%
“…The complexation of these receptors with two disaccharides was investigated by 1 H NMR spectroscopy and showed that the incorporation of the methyl carboxylate groups in 142 increased the association relative to the unfunctionalized derivative 141. A subsequent publication reported on the detailed binding affinities of square cyclophane 140 and tetrameric 141-143 [55] with mono-and disaccharide guests. In general, their findings showed that the smaller and more size complementary cyclophane 140 preferentially bound monosaccharide guests.…”
Section: Chiral Macrocycles Using Chiral Carbon-rich Building Blocksmentioning
confidence: 99%